Computer simulations of single particles in external electric fields. Issue 34 (14th September 2015) - Zhou, Jiajia; Schmid, Friederike
<x xml:space="preserve">Abstract</x> We review recent coarse-grained simulations of colloidal particles and polyelectrolyte chains in external electric fields.